Upaya Pengembangan Pariwisata Buntu Burake: Studi Kasus: Keamatan Makale, Kabupaten Tana Toraja - yiska aurora; Rudi Latief; Idris Taking (Journal of Urban Planning Studies, 2022)
This study aims to find out how much influence BuntuBurake Tourism has on the socioeconomics in the Buntu BurakeTourism area and to identify how efforts to ensure the development ofthe Buntu Burake Tourism area. This research is a consideration andreference material in analyzing descriptively. The variables of thisstudy include socioeconomics, Burake Dead End Tourism activities,Visitors, Facilities and Infrastructure. Correlation and descriptiveanlysis methods, in the influence of Burake Dead End Tourism onsocioeconomics and efforts to control socioeconomic activities.